The Analysis Source Text from the Novel with the Title “Chamber of Secret” written by JK Rolling with Using Software Monoconc Pro (MonoPro) - Novari, Ari Fajria (Universitas Mathla'ul Anwar Banten, 2019)
The purposes of this research is to analysis the source text from the novel with the title “chamberof the secret” written by JK Wrolling with using software monoconc Pro (MonoPro). This researchused software Monoconc Pro (MonoPro) Version 2.0 invented by Michael Barlow as a tool in theanalysis contributes a great role. As corpus software that functions to show the concordance ofwords, this tool starts the analysis by searching the focusing word ‘eyes’. Finding of this researchshowed that the making meaning is the most important aspect to avid readers since it is the placewhere the unity of the novel is. The research was done by using corpus-based analysis which itprovides objective result as it was gave evidences. In order to make meaning to the novel, theresearch made by searching on how the similarity of words that occur mostly in the novel andconclude the meaning by seeing on how they show based on its sentences and/ or its context asthis research has done.